A Single‐Layer Composite Separator with 3D‐Reinforced Microstructure for Practical High‐Temperature Lithium Ion Batteries. Issue 23 (8th May 2022) - Yuan, Botao; Liu, Jipeng; Dong, Liwei; Chen, Dongjiang; Zhong, Shijie; Liang, Yifang; Liu, Yuanpeng; Ji, Yuanpeng; Wu, Xiaoqiang; Kong, Qingquan; Han, Jiecai; He, Weidong
Abstract: Incorporation of ceramic materials into separators has been frequently applied in both research and industry to improve the overall high‐temperature performances of lithium ion batteries. However, inorganic ceramic particles tend to form aggregation in separators and even fall off in the separator matrix due to the inferior combination between ceramic particles and polymer matrix, giving rise to a decrease in separator porosity and thus the degradation of battery performances. Herein, a single‐layer core‐shell architecture is designed to reinforce the polymer matrix through encircling Al2 O3 particles by poly(vinylidene fluoride) with strong inter‐molecular interaction. The 3D‐reinforced microstructure effectively improves pore distribution and thermal stability to resist the dimensional deformation at high temperatures, thus giving rise to a high Coulombic efficiency of 99.16% and 87.5% capacity retention after 500 cycles at 80 ° C for LiFePO4 /Li batteries. In particular, the excellent performances of the proposed separator microstructure are confirmed with a thickness value of commercial separators. This work provides a promising strategy to fabricate a core‐shell structural composite separator for stable lithium ion batteries at high temperatures. Abstract : In this study, a single‐layer core‐shell architecture with strong inter‐molecular interaction is designed to reinforce the separator of poly(vinylidene fluoride) by encircling Al2 O3 particles with the polymer matrix. The 3D‐reinforced microstructure effectively improves pore distribution and thermal stability to resist the dimensional deformation at high temperatures, thus giving rise to high electrochemical performances for LiFePO4 /Li batteries.